The use of Flucarbazone-sodium to control wild oats (Avena spp.) in cultivated wheat fields of the Western Cape of South Africa - Bester, Dirk Wouter (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.